2022
DOI: 10.1186/s13052-022-01364-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased behavioral problems in children with sleep-disordered breathing

Abstract: Background Healthy sleep is essential for the cognitive, behavioral and emotional development of children. Therefore, this study aimed to assess the behavioral consequences of sleep disturbances by examining children with sleep-disordered breathing compared with control participants. Methods Seventy-eight children with SDB (average age: 6.7 years (SD = 1.83); 61 had OSA and 17 had primary snoring) and 156 control subjects (average age: 6.57 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…If left untreated, OSA can contribute to neurocognitive dysfunction in children in a dose-dependent manner, negatively impacting domains such as attention and memory [ 9 ]. A study by Csábi et al found that children with SDB had significantly higher attention-deficit/hyperactivity disorder (ADHD) scale ratings compared to age- and gender-matched controls, noting that even mild degrees of SDB are associated with emotional and behavioral difficulties in children [ 10 ]. Pediatric OSA also increases the risk of adverse cardiovascular and metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, OSA can contribute to neurocognitive dysfunction in children in a dose-dependent manner, negatively impacting domains such as attention and memory [ 9 ]. A study by Csábi et al found that children with SDB had significantly higher attention-deficit/hyperactivity disorder (ADHD) scale ratings compared to age- and gender-matched controls, noting that even mild degrees of SDB are associated with emotional and behavioral difficulties in children [ 10 ]. Pediatric OSA also increases the risk of adverse cardiovascular and metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, numerous studies have shown that children who suffer from SDB are at great risk for behavioral disorders, which may manifest in a variety of ways. The most commonly observed disorders are hyperactivity disorder, attention disorder, and somatic complaints ( 17 , 24 ). According to the results of CPRS among the three groups, the OSA children were found to have behavioral disorders, mainly learning problems and hyperactivity, whereas the PS children did not show any obvious behavioral disorders when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have examined neuropsychological and behavioral functioning in children with SDB [48][49][50] or snoring [47,51], through questionnaire-based designs [52] or before and after adenotonsillectomy [53]. Our retrospective cohort study addressed some additional key points in the current literature.…”
Section: Discussionmentioning
confidence: 99%